The emperor of Nihon-Ja - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2011)
In a faraway land, a young warrior must protect an emperor from an uprising and train an inexperienced army, with assistance from his Ranger friends.